The effect of the strategy of thinking methods in developing the skills of teaching the electronic class (CLASS ROOM) among students of the Arabic language departments in the colleges of education - Ghanem Abdul Hamza Al-Zalzali, Akram (Journal of College of Education, 2022)
SummaryThe current research aims to identify (the effect of the strategy of thinking methods in developing electronic classroom teaching skills (CLASS ROOM) for students of Arabic language departments in colleges of education).    The researcher followed the quasi-experimental approach, adopting the experimental design with partial control, which is the design of the control group with pre- and post-tests.    The research sample consisted of students of the Arabic Language Department of the fourth stage in the College of Education for Human Sciences, Al-Muthanna University, and the sample included (66) male and female students.    The researcher was rewarded between the two research groups in (chronological age calculated in months, previous year’s grades, intelligence test, pre-test for electronic classroom teaching skills).    The researcher himself studied the students of the experimental group using the thinking methods strategy, which was controlled in the usual way during the duration of the experiment, which lasted a whole semester (the first) of the academic year (2020-2021).    The researcher prepared a test for the skills of teaching the electronic class consisting of (20) paragraphs of the type of multiple choice, and applied it to the research sample before and after, and by using the statistical package (SPSS) in the research procedures and extracting the research result, the researcher reached the superiority of the students of the experimental group who studied with the strategy of methods of study. Thinking on the students of the control group in the post-test, and in light of the result, the researcher drew a number of conclusions, and recommended a number of recommendations, including (adopting the strategy of thinking methods in teaching students of Arabic language departments the fourth stage in teaching observation and practical application), and the researcher suggested (conducting a study Similar in other materials, and a similar study in other stages of developing similar variables).
Keywords: : thinking styles strategy, teaching skills, electronic class